Study on the performance and economy of the building-integrated micro-grid considering photovoltaic and pumped storage: a case study in Foshan. (17th May 2022) - Sun, Haitao; Ren, Qingzheng; Hou, Jili; Zhao, Zimo; Xie, Donghuan; Zhao, Wei; Meng, Fanbin
Abstract: Micro-grid is a promising technology for the energy reform in urban areas. This paper takes a building as a case study to construct a micro-grid system, which includes rooftop photovoltaic and pumped storage systems according to the characteristics of the building. Moreover, the cost–benefit analysis of the commercial building micro-grid system is also performed to obtain an in-depth understanding of the feasibility of the project. According to the characteristics of power load of commercial buildings, the working characteristics of the developed micro-grid and the mathematical model of optimal operation of micro-grid in commercial buildings is constructed. The calculation results from the mathematical model show that the dynamic payback period (PBP) of the micro-grid system of commercial buildings is 4.74 years, while the dynamic PBP of the micro-grid system of battery energy storage is 7.95 years. Therefore, the micro-grid system pumped storage has a much better economy than that with battery energy storage.